2017
DOI: 10.1002/jssc.201601343
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast liquid chromatography with tandem mass spectrometry determination of eight bioactive components of Kai-Xin-San in rat plasma and its application to a comparative pharmacokinetic study in normal and Alzheimer's disease rats

Abstract: A method of ultra-fast liquid chromatography with tandem mass spectrometry was developed and validated for the simultaneous quantitation of eight bioactive components, including polygalaxanthone III, sibiricaxanthone B, tenuifolin, sibiricose A5, sibiricose A6, tenuifoliside A, ginsenoside Re and ginsenoside Rb1 in rat plasma after oral administration of Kai-Xin-San. The plasma samples were extracted by liquid-liquid extraction using digoxin as an internal standard. Chromatographic separation was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Briefly, the AD rats were injected intraperitoneally with D-gal (50 mg/kg/mL) for 6 weeks and the control group was given the same volume of saline. Six groups of AD rats were administered intragastrically with KXS (10.0 g/kg), GR (3.0 g/kg), PR (2.0 g/kg), PO (3.0 g/kg), AT (2.0 g/kg), and Hup A (0.027 mg/kg) once a day from the third week until the end of the experiment [25]. At the end of the fourth week, the stereotaxic injection of 4 μg Aβ [25][26][27][28][29][30][31][32][33][34][35] (1 μg/μL) was operated at the following coordinates: anteroposterior-3.5; mediolateral-+2.0; and dorsoventral-2.8 mm [26].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Briefly, the AD rats were injected intraperitoneally with D-gal (50 mg/kg/mL) for 6 weeks and the control group was given the same volume of saline. Six groups of AD rats were administered intragastrically with KXS (10.0 g/kg), GR (3.0 g/kg), PR (2.0 g/kg), PO (3.0 g/kg), AT (2.0 g/kg), and Hup A (0.027 mg/kg) once a day from the third week until the end of the experiment [25]. At the end of the fourth week, the stereotaxic injection of 4 μg Aβ [25][26][27][28][29][30][31][32][33][34][35] (1 μg/μL) was operated at the following coordinates: anteroposterior-3.5; mediolateral-+2.0; and dorsoventral-2.8 mm [26].…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Briefly, AD rats were injected with D-gal (50 mg/kg/d) intraperitoneally for 6 weeks, and control rats were given the same volume of saline. KXS (10 g/kg/d) and Hup A (30 μ g/kg/d) were oral administrated from the third week until the end of the experiment once a day [10]. The stereotaxic injection of 4 μ g A β 25-35 (1 μ g/ μ L) was operated as described previously [11].…”
Section: Methodsmentioning
confidence: 99%
“…For the past few years, many researches have focused on this issue. They found that pathological factors such as liver injury, diabetes, stroke, fever, rheumatoid arthritis, migraine, coronary atherosclerotic heart disease, cancer, and neurodegenerative diseases demonstrate deep impact on metabolism of HRC [8, 6775]. Hepatocytes are the parenchymal cells of liver which can improve the excretion of xenobiotics through urine or feces by modifying their structure, including phase I xenobiotic metabolism like oxidation or hydrolysis, followed by phase II metabolism like glucuronidation, sulfation, acetylation, or glutathione conjugation.…”
Section: The Influence Of Pathological Statusmentioning
confidence: 99%